A abordagem construtivista na aprendizagem da matemática com a utilização de recursos didáticos e objetos de aprendizagem - Calvalcante, Tábita Viana (Universidade Federal Rural do Semi-Árido, 2019)
The present work aims at fomenting the use of educational resources and learning objects guided towards to teaching of diverse math contents. Plus, it suggests the use of a constructivist approach to teaching, instead of the traditional one. Based on Constructivism, it is considered that knowledge can be acquired through spontaneous actions, where the teacher is in charge of instigating the curiosity, interaction and student’s participation on learning. Through an experimental study, it aims to evaluate if the use of these resources in Mathematics classes foment a better output in students' performance and arouse curiosity and investigation on them.The experimental group had access to didactic resources and learning objects allied to the proposal of constructivist teaching and the control group had access to the didactic resource limited to book, board and marker allied to the traditional teaching approach. The results showed that the experimental group had a better performance in relation to the control one
Keywords: Construtivismo; Recursos didáticos; Objetos de aprendizagem; Ensino de matemática; Ensino médio; Constructivism; Teaching resources; Learning objects; Match instruction; High school; CIENCIAS EXATAS E DA TERRA::MATEMATICA